THE EFFECTIVENESS OF GIVING HEALTH EDUCATION NURSING ACTIONS TO A HYPERTENSION FAMILY WITH A KNOWLEDGE DEFICIT IN PUCANGSEWU - Ryanda Fikri Husein; Linggar Rolis Kumara; Pramono Giri Kriswoyo (Jurnal Keperawatan Respati Yogyakarta, 2021)
Hypertension is the most common disease suffered by the community. Hypertension can cause complications if not treated quickly and make the patient's condition worse. Heart attacks and strokes are examples of complications caused by hypertension. Hypertension is a major health problem. The World Health Organization (WHO) and the International Society of Hypertension (ISH) say there are about 600 million cases of hypertension worldwide. In society, knowledge about hypertension management is still very low. So that one of the efforts that can be done is to conduct health education (penkes). Health education is a process that can increase a person's degree and awareness about health. Families can be influential in controlling a disease. Inharmonious family relationships, lack of attention from family, and lack of family knowledge that make inability in patient care greatly affect patient recovery. The writing method used in this case study is descriptive analytic method, namely case presentation with a nursing process approach that focuses on one important problem in the selected case. With a focus on the study of knowledge deficits related to the inability of families to recognize family health problems. The results of the study showed that the provision of nursing care to hypertensive patients with a focus on knowledge deficiency studies through health education interventions (penkes) showed an improvement in conditions where patients and their families knew more about hypertension diets, Keywords: nursing care; knowledge deficiency; health intervention.